Remote control: Horizontal surveillance and the gendering of carceral punishment - Gibson-Light, Michael (Theoretical criminology, 2023)
Research traditionally suggests that men incarcerated in the USA regard horizontal surveillance—that is, monitoring the behaviors of other prisoners—as antithetical to notions of masculinity behind bars. Yet, following an 18-month ethnography in a US prison for men, this article reveals that the imprisoned may in fact embrace prisoner-on-prisoner monitoring tied to labor. It details how participants in this institution sought out peer surveillants who had the power to grant referrals to more desirable jobs. Within prison worksites, individuals further policed peers’ production and service quality. Labor-based horizontal surveillance was integral to performances of masculinity related to employment status and work ethic. Drawing on labor scholarship as well as studies of surveillance in other penal settings, this article reveals how supervision maps onto gendered beliefs about work, offending, and contemporary American corrections in ways that contribute to carceral agendas and broader systems of control.